2016
DOI: 10.1038/srep35146
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow-derived macrophages distinct from tissue-resident macrophages play a pivotal role in Concanavalin A-induced murine liver injury via CCR9 axis

Abstract: The fundamental mechanism how heterogeneous hepatic macrophage (Mφ) subsets fulfill diverse functions in health and disease has not been elucidated. We recently reported that CCR9+ inflammatory Mφs play a critical role in the course of acute liver injury. To clarify the origin and differentiation of CCR9+Mφs, we used a unique partial bone marrow (BM) chimera model with liver shielding for maintaining hepatic resident Mφs. First, irradiated mice developed less liver injury with less Mφs accumulation by Concanav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 50 publications
4
17
0
Order By: Relevance
“…) macrophages play a critical role in Con A-induced acute liver injury by inducing Th1 responses (16,17). Consistently, CCR9 expression in DW-Con A macrophages was significantly elevated, whereas DSS-Con A macrophages lacked CCR9 expression.…”
Section: Resultssupporting
confidence: 51%
See 1 more Smart Citation
“…) macrophages play a critical role in Con A-induced acute liver injury by inducing Th1 responses (16,17). Consistently, CCR9 expression in DW-Con A macrophages was significantly elevated, whereas DSS-Con A macrophages lacked CCR9 expression.…”
Section: Resultssupporting
confidence: 51%
“…We recently reported the critical role of TNF-α-producing CCR9 + CD11b + macrophages in the pathogenesis of Con A-induced hepatitis (16,17). These macrophages are characterized as classically activated macrophages that contribute to host defenses against a variety of bacteria and viruses and play a substantial role in antitumor immunity.…”
Section: Discussionmentioning
confidence: 99%
“…However, splenectomy in WT mice did not attenuate ConA hepatitis at 24 h, suggesting that the spleen by itself is not responsible for the severity of the disease. Consistent with this, splenectomy 2 weeks before ConA treatment did not affect liver injury induced by ConA treatment [28]. However, ALT levels in splenectomized Ramp1 −/− mice fell by 50% at 24 h after ConA treatment when compared with those in sham-operated Ramp1 −/− mice, suggesting that RAMP1 signaling in splenocytes improves ConA-mediated hepatitis.…”
Section: Discussionsupporting
confidence: 52%
“…( ) HSCs relay inflammatory signals ( ) ; they have also been shown to participate in inflammatory macrophage differentiation and local proliferation in a murine concanavalin A acute liver injury model. ( ) Using a murine tetrachloride liver fibrosis model, Issa et al ( ) showed that a mutation in collagen‐I that confers resistance to collagenase degradation resulted in diminished stellate cell apoptosis and impaired hepatocyte regeneration. Activated HSCs participate in the termination of hepatocyte regeneration, probably through the elevated expression of transforming growth factor β, a well‐known hepatocyte antiproliferative factor, as demonstrated in various murine models of liver fibrosis.…”
Section: Discussionmentioning
confidence: 99%